2021
DOI: 10.1186/s42269-021-00588-w
|View full text |Cite
|
Sign up to set email alerts
|

The new trending pain-free cesarean section: TAP block versus IV PCA

Abstract: Background Women's pain satisfaction post-cesarean section remains a challenge. Accurate assessment of pain severity of post-cesarean section helps to choose the most appropriate anesthetic approach, drug, and dose, as well as improvement of treatment of postoperative pain. Our objective was to compare the efficacy of ultrasound-assisted transversus abdominis plane (TAP) block versus IV patient-controlled analgesia (PCA) in the first 24 h postoperative in women who underwent cesarean section. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…With the increase of caesarean sections worldwide, the management and treatment of LAST in pregnant women is an increasingly important issue [ 63 ]. Anaesthetists use local anaesthesia more often than general anaesthesia in pregnant women [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increase of caesarean sections worldwide, the management and treatment of LAST in pregnant women is an increasingly important issue [ 63 ]. Anaesthetists use local anaesthesia more often than general anaesthesia in pregnant women [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been increased used of other analgesic modalities following caesarean delivery. 23 25 TAP block has been advocated recently. 23 , 24 A previous study compared multimodal analgesia similar to this current study with TAP and found less need for opioids and better VAS scores.…”
Section: Discussionmentioning
confidence: 99%
“… 23 25 TAP block has been advocated recently. 23 , 24 A previous study compared multimodal analgesia similar to this current study with TAP and found less need for opioids and better VAS scores. 31 Other studies have shown more beneficial effects of TAP compared with opioids and NSAIDs when used alone or in combination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations